Ensuring the Fulfillment of Contracts in Civil Law - Puchkovska, Iryna Y.; Pecheniy, Oleg P.; Isaiev, Arsen M. (International Journal of Criminology and Sociology, 2021)
The main purpose of the article is to comprehensively describe the main ways to ensure compliance. The main research approach is analytical and legal methodology. Doctrinal and legislative provisions on ensuring the implementation of civil law agreements were analysed. The process of formation of the institute ensuring the fulfilment of contracts was characterised. A comparative analysis of ways to ensure the implementation of agreements on their legal nature and effectiveness, highlighted the signs of their demarcation. The foreign practice of ensuring the fulfilment of contractual obligations was analysed, and the possible directions of its implementation in the domestic legal space were determined. Gaps in legislative regulation and problems of practical implementation in ways to ensure the implementation of agreements were identified. The author proposed the definition of ways to ensure the implementation of contracts. The findings are valuable for legislative initiatives and for the practical activities of the parties to contractual obligations in terms of choosing the most effective way to secure the contracts they enter into.